Exploring the ‘Shadows’ in the Implementation Processes for National Anti-fraud Strategies at the Local Level: aims, Ownership, and Impact - Levi, Michael (European journal on criminal policy and research, 2020)
This article studies the development and implementation of a nationally drafted strategy for fraud in local government in England. The purpose, relevant to other countries which also face (or evade) problems of policy outreach, is to consider what is required to achieve effective implementation through three broad aspects: aims, ownership, and impact. There is a particular focus on the assessment of the strategy implementation process and what mechanisms translate strategies into effective delivery or what other factors may subvert that delivery. The empirical research draws on the UK government’s 2006 policy review on fraud and the consequential changes between then and 2019, including a number of fraud strategies initiated by the United Kingdom central government. To review implementation in practice, it focuses on the 2011 local government strategy and uses a local-level case study to assess issues concerning aims, ownership, and impact, as well as the effect of other nationally determined policies and agendas. It concludes that without an ‘owned’ strategy implementation process as a whole, national strategies concerning the prevention and policing of fraud in England in the twenty-first century have had—and continue to have—modest impact on practice on the ground at the local level. We find it plausible that this is true elsewhere in the world, not only for crime control but also for other ‘change’ strategies in the public sector. However, testing that proposition is for researchers in other countries. Our aim here is to use this superficially parochial study to raise more universal questions about how policy designers (and academic researchers) need to take better account of circumstances on the ground, the management of strategy implementation and legitimacy, if their strategies are to be more than merely symbolic rhetoric.